Household consumption and the housing net worth channel in Ireland - David Cronin; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2021)
The performance of the Irish economy over the period 2002-2019 varied considerably, with a credit-led boom up to 2007 being followed by a sharp fall in economic activity and house prices in the following five years. This provides a valuable sample for investigating the relevance of the housing net worth channel to consumption developments. The evidence presented here indicates the channel being active during the 2007-2012 downturn with a fall in house prices causing a decline in consumption. It does not have an impact outside that downturn. Consequently, the results add to the international evidence of how an accumulation of household debt and a downturn in house prices has a substantial adverse impact on consumption.
Keywords: C22; E21; R21; 330; housing net worth channel; consumption; household debt